Έλεγχος αξιοπιστίας διαφορικών ενεργών διατομών ελαφρών στοιχείων σε περιοχή ενδιαφέροντος EBS (Elastic backscattering spectroscopy) και NRA (Nuclear reaction analysis) - Δέδε, Στεφανία (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών. Τομέας Φυσικής, 2016)
The benchmarking experimental procedure in IBA (Ion Beam Analysis) is carefully designed in order to validate differential cross–section data of charged particles via the acquisition of EBS and NRA spectra from thick targets of known composition, followed by their simulations. The importance of the benchmarking procedure lies in the requirements of the IBA depth profiling techniques. All of these techniques depend largely on the accuracy of the available differential cross sections for the reactions involved, which are unfortunately quite rare and usually discrepant. This means that their reliability is questionable at best, thus a carefully designed benchmarking procedure is essential. Moreover, benchmarking can provide the necessary feedback for small adjustment of the parameters of the nuclear model used in the evaluation process and also indicate the best experimental datasets if evaluated data are not available. In the present work, such benchmarking measurements have been performed at the laboratory of the Institute for Nuclear and Particle Physics “Demokritos”, for the elastic scattering of protons on natSi and 27Al in the energy range of 1.1 – 3.5 MeV at four backward angles, at 140o, 150o, 160o and 170o. In addition, we performed measurements for the elastic scattering of deuterons on 12C and 16O in the energy range of 1.1 – 1.9 MeV at four backward angles, at 140o, 150o, 165o and 170o. More specifically, we used a thick non–polished Si target with Au evaporated on top, a thick polished C and a thick polished Al target with Au evaporated on top and a Nb2O5 tablet. The spectra acquired were compared with simulated ones using the SIMNRA program along with the evaluated differential cross-section datasets from IBANDL. All the experimental parameters were thoroughly investigated. The obtained results, the discrepancies we found and the problems we faced during the benchmarking process are discussed and analyzed.